Предмет: Алгебра,
автор: belfeek
Определите a и b зная, что:
А) 3х = (а+b)x + 2a - b
B) ( x+a)(bx-1) = x^2 - 7x + 6
Ответы
Автор ответа:
0
A)3x=(a+b)x+2a-b
3x=ax+bx+2a-b
-ax-2a=bx-b-3x
a(-x-2)=bx-b-3x
a=bx-b-3x/(-x-2)
3x=ax+bx+2a-b
b-bx=ax+2a-3x
b (1-x)=ax+2a-3x
b=ax+2a-3x/(1-x)
3x=ax+bx+2a-b
-ax-2a=bx-b-3x
a(-x-2)=bx-b-3x
a=bx-b-3x/(-x-2)
3x=ax+bx+2a-b
b-bx=ax+2a-3x
b (1-x)=ax+2a-3x
b=ax+2a-3x/(1-x)
Похожие вопросы
Предмет: Музыка,
автор: Аноним
Предмет: Математика,
автор: marinasokolenko2009
Предмет: Алгебра,
автор: ostapenkoveronika0
Предмет: Математика,
автор: olehcka1101